2019
DOI: 10.1021/acscombsci.9b00152
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Protein Tyrosine Phosphatase Specificity with Self-Assembled Monolayers for Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry and Peptide Arrays

Abstract: The opposing activities of phosphatases and kinases determine the phosphorylation status of proteins, yet kinases have received disproportionate attention in studies of cellular processes, with the roles of phosphatases remaining less understood. This paper describes the use of phosphotyrosine-containing peptide arrays together with MALDI mass spectrometry to directly profile phosphatase substrate selectivities. Twenty-two phosphotyrosine phosphatases were characterized with the arrays to give a profile of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Remarkably, the rule we describe—where PTPs disfavor basic residues proximal to pY—is surprisingly general. In this work, we show how this insight can explain signaling in β-cat mutants and in previous work we addressed its role in insulin receptor 22 . We note that our database search identified over 6000 relevant cancer mutations that could employ this missense mutation/PTP restriction mechanism, and suggests that this mechanism can have a broad relevance in understanding mutations that underlie cancers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Remarkably, the rule we describe—where PTPs disfavor basic residues proximal to pY—is surprisingly general. In this work, we show how this insight can explain signaling in β-cat mutants and in previous work we addressed its role in insulin receptor 22 . We note that our database search identified over 6000 relevant cancer mutations that could employ this missense mutation/PTP restriction mechanism, and suggests that this mechanism can have a broad relevance in understanding mutations that underlie cancers.…”
Section: Discussionmentioning
confidence: 84%
“…In recent work, we used peptide arrays and SAMDI-MS 15 21 (self-assembled monolayers for matrix-assisted laser desorption/ionization mass spectrometry) to profile the specificities of 22 phosphatases including PTP1B, TC-PTP, MEG1, SHP1, PTPN7, MEG2, SHP2, PTPN12, PTPN13, PTPN14, PTPRA, PTPbeta, CD45, PTPRE, RPTPG, DEP1, PTPmu, PTPsigma, PRL1-3 and hALP (Fig. 1 ) 22 . We found that most of the PTPs lack activity towards substrates that have an arginine (R) or lysine (K) residue adjacent to the phosphotyrosine (pY).…”
Section: Introductionmentioning
confidence: 99%
“…After purification, the RST can be removed using either these proteases or SUMO protease (for RST N ). Treatment with TEV leaves a GC scar at the N-terminus, where the cysteine is included for SAMDI (self-assembled monolayers on gold for matrix-assisted laser desorption/ionization) mass spectroscopy [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Solid-phase peptide synthesis (SPPS) was performed as described previously . Briefly, SPPS was performed on Rink-amide resin (10 mg) housed in 96-well filter plates.…”
Section: Methodsmentioning
confidence: 99%